Healable Structure Triggered by Thermal/Electrochemical Force in Layered GeSe2 for High Performance Li‐Ion Batteries. Issue 18 (12th March 2018) - Wei, Yaqing; Huang, Liang; He, Jun; Guo, Yanpeng; Qin, Ruihuan; Li, Huiqiao; Zhai, Tianyou
Abstract: The metal sulfide or selenides have attracted increasing attention for high‐energy lithium‐ion batteries due to their unique layer structure flexibility, higher conductivity, and lower voltage polarization than metal oxides. However, low initial coulomb efficiency (ICE), serious structure destruction, and irreversible bonding chemistry are still big challenges for their practical application. Herein, layer GeSe2 and its carbon composite are synthesized by high‐energy ball milling and it is surprisingly found that crystalline c‐GeSe2 possesses higher reversible capacity and better rate performances than their amorphous counterparts. More specially, the broken GeSe bondings upon lithiation are also observed to regenerate after delithiation. These unusual phenomena are investigated by both experimental tools and theoretical calculations. Compared to other typical MX2 (M = Mo, W, X = S, Se), the electronegativity of Ge is more close to selenium and the formation energy of GeSe bonding is much smaller. Thus, a mild driven force such as thermoheating at low temperature can recover the ordered layer structure, helping to heal the high conductivity and unimpeded Li diffusion pathways for crystalline GeSe2 . Similarly, electrochemical delithium force also triggers the rebuilding of GeSe bonding upon Li‐extraction, boosting GeSe2 /C with large capacity (1050 mA h g −1 ), ultrahigh ICE (94%), and cycling stability. Abstract : Due to the low formation energy of GeSe bondings, a mild driven force such as thermoheating can recover the ordered layer structure, helping c‐GeSe2 to get better rate performances than its amorphous counterparts. Electrochemical delithium force also triggers the rebuilding of GeSe bonding upon Li‐extraction, boosting GeSe2 /C with large capacity (1050 mA h g −1 ), ultrahigh initial coulomb efficiency (94%), and cyclability.